A novel strigolactone‐miR156 module controls stomatal behaviour during drought recovery. (30th March 2020) - Visentin, Ivan; Pagliarani, Chiara; Deva, Eleonora; Caracci, Alessio; Turečková, Veronika; Novák, Ondrej; Lovisolo, Claudio; Schubert, Andrea; Cardinale, Francesca
Abstract: miR156 is a conserved microRNA whose role and induction mechanisms under stress are poorly known. Strigolactones are phytohormones needed in shoots for drought acclimation. They promote stomatal closure ABA‐dependently and independently; however, downstream effectors for the former have not been identified. Linkage between miR156 and strigolactones under stress has not been reported. We compared ABA accumulation and sensitivity as well as performances of wt and miR156‐overexpressing (miR156‐oe) tomato plants during drought. We also quantified miR156 levels in wt, strigolactone‐depleted and strigolactone‐treated plants, exposed to drought stress. Under irrigated conditions, miR156 overexpression and strigolactone treatment led to lower stomatal conductance and higher ABA sensitivity. Exogenous strigolactones were sufficient for miR156 accumulation in leaves, while endogenous strigolactones were required for miR156 induction by drought. The "after‐effect" of drought, by which stomata do not completely re‐open after rewatering, was enhanced by both strigolactones and miR156. The transcript profiles of several miR156 targets were altered in strigolactone‐depleted plants. Our results show that strigolactones act as a molecular link between drought and miR156 in tomato, and identify miR156 as a mediator of ABA‐dependent effect of strigolactones on the after‐effect of drought on stomata. Thus, we provide insights into both strigolactone and miR156 action on stomata. Abstract : Strigolactones are phytohormones important for effective drought responses, and miR156 is a conserved microRNA induced by environmental stress. This work identifies strigolactones as triggers of miR156 induction under drought in tomato. It also correlates miR156 with the strigolactone‐ and ABA‐dependent promotion of sustained stomatal closure after rewatering. Thus, a novel strigolactone‐miR156‐ABA module is uncovered that is important for the stomatal memory of drought.